DIGITALISASI EKONOMI SYARIAH - AAN ANSORI (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2016)
Abstract. Digitalization of Islamic Economics. Digitizing sharia economy can be expanded in various economic aspects of both microeconomics and macroeconomics. Now, the role of digital is very unusual, almost all economies using information and communication technologies or digitalisation, both in packaging products or in marketing the product, making it easier and quicker distribution of information used to make economic growth more quickly and there is no limit to the support digital technology and information technology. Information technology has penetrated keindividu (personal) can support the digitization era of information and communication in the conventional economy and sharia economy, the technology is now in the palm of your hand gadgets such as mobile applications that can be downloaded and installed with features easily understood by the user. Similarly, in the world of banking, Islamic banking in conducting its activities in cooperation with information technology to establish Islamic banking information system by creating a special application (app) that can simplify all the processes of ownership in the existing transaction. Establishment of the digital society as a result of the accelerated by the development and application of information and communication technology is very intensive in all fields of economy, marketing, finance, services, education and so forth. Thus, digitization is formed to allow users in the transaction, so that the economy increased.Abstrak. Digitalisasi Ekonomi Syariah. Digitalisasi ekonomi syariah dapat merambah dalam berbagai aspek ekonomi baik ekonomi mikro maupun ekonomi makro. Sekarang ini peran digital sangat luar biasa, hampir semua perekonomian menggunakan teknologi informasi dan komunikasi atau digitalisasi, baik dalam mengemas produk ataupun dalam memasarkan produk, sehingga lebih  mudah dan  lebih cepat dalam distribusi informasi yang digunakan untuk membuat pertumbuhan ekonomi semakin cepat dan tiada batas dengan dukungan teknologi digital dan teknologi informasi. Teknologi informasi yang sudah merambah keindividu (personal) dapat mendukung era digitalisasi informasi dan komunikasi pada ekonomi konvensional maupun ekonomi syariah, teknologi tersebut sekarang sudah dalam genggaman tangan pengguna gadget seperti aplikasi mobile yang dapat diunduh dan dipasang dengan fitur mudah dimengerti oleh user. Demikian pula di dunia perbankan, dalam melakukan kegiatannya perbankan syariah bekerja sama dengan bidang teknologi informasi untuk membangun sistem informasi perbankan syariah dengan membuat aplikasi khusus (app) yang dapat mempermudah semua proses-proses transaksi yang ada diperbankan. Terbentuknya masyarakat digital akibat dari tersebut dipacu oleh perkembangan dan penerapan teknologi informasi dan komunikasi yang sangat intensif di semua bidang baik ekonomi, pemasaran, keuangan, jasa, pendidikan dan sebagainya. Maka, digitalisasi terbentuk untuk memudahkan pengguna dalam melakukan transaksi, sehingga perekonomian meningkat.